1997
DOI: 10.1099/00221287-143-5-1575
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation of ‘non-culturable’ cells from aged cultures of Campylobacter jejuni

Abstract: When stationary phase batch cultures of Csmpylobacter jejuni were stored in sealed flasks under static conditions, viable numbers declined from 2 x lo9 c.f.u. ml'' to around 103-106 c.f.u. ml'l within 4-6 weeks. When the aged cultures were sparged with a microaerobic gas mixture, there was a rapid increase in viable numbers accompanied by a change from predominantly coccoid t o vibrioid morphology. The most probable number (MPN) technique was used to distinguish resuscitation of injured or dormant cells from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…The differences between both types of assays can be explained in part by the greater stringency of the broth microdilution assay, i.e., after the killing reaction has been terminated by dilution, surviving microorganisms form single colonies on agar plates but can fully outgrow in liquid media. Additionally, the conditions for resuscitation of sublethally damaged cells seem to be more favorable in the broth microdilution assay than in direct plating on agar media (4,43). Colony count assays performed with minimal media containing 1:100-instead of 1:1,000-diluted TSB showed only a marginal increase in bacterial growth for the investigated species and a markedly increased bacterial survival (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between both types of assays can be explained in part by the greater stringency of the broth microdilution assay, i.e., after the killing reaction has been terminated by dilution, surviving microorganisms form single colonies on agar plates but can fully outgrow in liquid media. Additionally, the conditions for resuscitation of sublethally damaged cells seem to be more favorable in the broth microdilution assay than in direct plating on agar media (4,43). Colony count assays performed with minimal media containing 1:100-instead of 1:1,000-diluted TSB showed only a marginal increase in bacterial growth for the investigated species and a markedly increased bacterial survival (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A link between CF and the VBNC form was noticed in a variety of microorganisms, for example, Actinomyces radicidentis [32], V. vulnificus [33], V. cholera [34], Mycobacterium smegmatis [35] and Salmonella typhimurium [36]. Association of CF with the VBNC state of C. jejuni would help to explain the incidences of infections by Campylobacter with no discernable environmental source [37].…”
Section: Properties Of Coccoid Formsmentioning
confidence: 99%
“…Sanders et al (2007) also showed that C. jejuni enters the VBNC state in biofilms (34). Bacteria in the VBNC state can be resuscitated by laboratory animal challenge and mucin treatment (2,3,5,33). Although the significance of this state in the transmission of C. jejuni infection is uncertain, it has been reported that the development of the VBNC state could be a survival strategy in aquatic environments (22,42,45).…”
Section: Biofilm Formationmentioning
confidence: 99%